Accumulative Roll Bonding of precipitation-hardenable aluminum alloys of the 6000 series in a warm rolling process - Merklein, Marion; Herrmann, Jürgen (Proc. ROLLING Conference, 2016)
In several industrial fields there is a persistent trend to lightweight construction. An auspicious possibility to cope with this challenge is the application of high strength aluminum, produced by accumulative roll bonding (ARB). Key idea of the ARB approach, which was originally invented by Saito et al. (1998), is the subsequent stacking and rolling of sheet material in order to gain an ultrafine-grained microstructure. The grain refinement results from the high deformations and shear stresses during each cycle of ARB. At the moment aluminum alloys of the 6000 series are pre-heated and rolled at room temperature. Within this contribution sheets of an AA6014 alloy are manufactured in a warm rolling process for the first time. The aluminum sheets are characterized regarding their mechanical properties and in particular their flow behavior. Furthermore, the bond strength of the respectively last bonded layer is examined using T-peel tests. Both testing methods are carried out after two and four rolling cycles. Based on these investigations a process strategy for the production of multilayered sheets in a warm rolling process is derived.
EAM Import::2019-03-13